The effect of invasive strategy versus conservative strategy on mortality in patients with non-ST-elevation myocardial infarction at Sardjito Hospital Yogyakarta - Pradhana, Aditya; Bagaswoto, Hendry Purnasidha; Saputra, Firandi; Setianto, Budi Yuli (Universitas Brawijaya, 2025)
BACKGROUND: Acute myocardial infarction (AMI) causes high hospital admission rates and mortality in Indonesia. Previous studies showed that invasive strategies on non-ST-elevation myocardial infarction (NSTEMI) patients can provide more benefit in clinical outcomes, particularly in high- and very high-risk groups. However, this strategy cannot be implemented due to transportation limitations or a lack of available catheterization facilities in some regions. Recent meta-analyses suggested that early invasive strategies (≤24 hours), delayed strategies (>24 hours), or conservative showed no differences significantly in mortality rates from any cause, stroke or cardiovascular death in NSTEMI patients. OBJECTIVES: This study aims to define the impact of invasive strategies on in-hospital mortality in high and very high-risk NSTEMI patients at Sardjito Hospital. METHODS: A retrospective cohort study utilized data from 326 NSTEMI patients who satisfied the inclusion and exclusion criteria, obtained from the Sardjito Cardiovascular Intensive Care (SCIENCE) registry between January 2023 and June 2024. RESULTS: The invasive and conservative method groups did not substantially differ in in-hospital mortality among NSTEMI patients in either unadjusted (p=0.09) or adjusted analysis (p=0.071, OR 2.251, 95% CI [0.932–5.434]). However, a significant difference was found in the high-risk group (p=0.042) but not in the very-high-risk group (p=0.525). Multivariate analysis confirmed Killip classification (p=0.000, OR 4.449, 95% CI [2.195–9.016]) and hs-Troponin T levels (p=0.006, OR 1.000, 95% CI [1.000–1.000]) as independent mortality predictors. CONCLUSION: Invasive management gave high-risk NSTEMI patients a survival advantage over conservative therapy at Sardjito Hospital, but not in the very-high-risk population.